واقع مهارات حل المشكلات في مادة علم الأحياء لدى تلامذة الصف السابع الأساسي دراسة ميدانية في مدينة اللاذقية. (Journal of Hama University, 2024)
The aim of the current research was to identify the degree of possession of the Seventh grade students Problem-solving skills  in biology. The sample consisted of (250) students and students, randomly selected from (7) schools in Lattakia. The research is an achievement test for  Problem-solving skills. It consists of (18) multiple choice questions and the generation of alternatives. The veracity of the tool has been verified by presenting it to a group of arbitrators. The stability of the tool has been confirmed by a survey sample, (0.70).   After applying the tool and analyzing the results, the researcher reached a low level of possession of the Seventh grade students for  Problem-solving skills in general. The percentage of proficiency was (52.17%), which is less than the required limit (70%).   The results of the study showed that there were varying levels of proficiency of the sample for  Problem-solving skills. The sample achieved the level of proficiency in  the defining the problem and choosing the best alternative in percentages of (83.87%) and (76.13%) respectively, The percentages of proficiency  by percentage(14.93%),. Researcher with a number of relevant proposals to continue the research, the most important of which was:1_ descriptive study of the role of teachers in the development of  Problem-solving skills of students in the basic education stage. 2_ An analytical study of the books of  biology in the basic education stage; to know the extent of the inclusion of the  Problem-solving  skills.